Improvement of gas supply systems for industrial furnaces - Unaspekov, Берикбай; Abdukalikova, Гульнара; Apenov, Асылбек (Рroblems of engineering and professional education, 2023)
The article deals with questions related to the problems of improving the systems of gas protection of industrial furnaces. The distribution of heat in the feed system and the firing region using hot zone ejector units was analyzed on a mine scale. Zhûmystyq kenistıktegi en zhogary temperature (1800-1850 C) salkyndatu aimaygyan shyqqan ystyq auany paidalanggan kezede bolatyny analyticalq turde anyqtalgan. The system of supplying fuel and hot air to the working engine is fully described.